Teaching Vocabulary With Wordcard Games - Sartika Andi Patau (Sintuwu Maroso Journal of English Teaching, 2020)
The objectives of the research are to describe the process of English teacher use word card game in teaching vocabulary to the first grade students at SMP Sintuwu Maroso Poso. The method of the research is qualitative descriptive. The source of this research is taken from the first year students of SMP Sintuwu Maroso Poso. The number of the students are 23 students. The finding of the research is the process of teaching and learning vocabulary using wordcard game during the three meeting in the class were implemented well. The teaching vocabulary using wordcards applied with kinds of games. The games were (1) Guess my word, (2) De-vowelled words and (3) Ghostwriting. Every meeting consists of some steps, they are: The first step is motivating strategy. Motivating strategy consist of greeting and warming up. The second step is presentation strategy. The teacher starts to write the new word on the board give the explanation about the word and the meaning of the word. The teacher also applied games in presenting the vocabulary to the students. The third is skill practice. The fourth step is assessment. The fifth step is closing.